Elements of a standard criminalizing domestic violence - Ahmed, Rami; Abdulmenem , Feras (Journal of Legal Sciences, 2022)
Domestic vilonce comprises a unique privacy regarding indictment and eliminating such a behviour requires a precise standard for the sake of punishing those involved and also requires to be controlled in order not to be mishandled by others. This is imprtant for this behviour to be included by the lawful model that provides a punishment frame. This has drvied the researcher to start this study with this elements that formulate a criterion for indictment such a behviour. and in the same way the researcher has covered the family limits that includes the history of the marriage relationship, ending with what has the lawgiver set of limits and affinity degree in addition to the fact that the currnt study has tackles with the motives that rrally lead to domestic vilonce to lift any hazy states that may affect the lawgiver when modifying the event presented to him in order to set unique punishment according to the circumstances that drove the criminal to practice such a behviour against his family.